2016
DOI: 10.1007/s11136-016-1296-4
|View full text |Cite
|
Sign up to set email alerts
|

Individuals’ quality of life linked to major life events, perceived social support, and personality traits

Abstract: This study highlights the negative but temporary association between critical events and QoL. However, a combination of high conscientiousness and extraversion, and positive social support may explain better variances for a high-perceived QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
53
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 44 publications
8
53
0
1
Order By: Relevance
“…These findings failed to be replicated with other data. Yap et al (2012), Anusic et al (2014a) and Pocnet et al (2016) show no particular buffering effects of the Big Five personality on the respondents' SWB to major life events such as widowhood or unemployment.…”
Section: Literature Reviewmentioning
confidence: 84%
“…These findings failed to be replicated with other data. Yap et al (2012), Anusic et al (2014a) and Pocnet et al (2016) show no particular buffering effects of the Big Five personality on the respondents' SWB to major life events such as widowhood or unemployment.…”
Section: Literature Reviewmentioning
confidence: 84%
“…Previous studies have indicated that HRQOL is influenced by both personality and coping [ 38 ]. However, there is the need for inclusion of other relevant psychological variables, in addition to personality and coping, in the analytical models and studies [ 39 ]. This is important taking into account that HRQOL is a multidimensional construct that has been under-investigated for a long time in young populations in developing countries [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above mentioned existing literature, neuroticism, occupational stress, job satisfaction, and QOL are related and have complex relationships. Although the single effect of neuroticism [34], occupational stress [12], and job satisfaction [13] on QOL have been previously studied, their synergistic effects on QOL and the potential mechanism remain unclear. Therefore, the current study aims to fill this gap.…”
Section: Introductionmentioning
confidence: 99%